Laser Optoacoustical Method for Investigation of Some Physical Properties of Oil and Petroleum - Musayev, M.A.; Abbasov, I.I. (Наносистеми, наноматеріали, нанотехнології, 2017)
The laser generation of sound waves in strongly absorbing liquids is discussed. We demonstrate the experimental method to determine simultaneously both velocity of sound and light-absorption coefficient in liquids. With this method, measurements of these values for different oils are carried out, and the temperature coefficients of velocity of sound and gummosity are determined. Обсуждается лазерная генерация звуковых волн в сильно поглощающих жидкостях. Мы демонстрируем экспериментальный метод для одновременного определения скорости звука и коэффициент поглощения света в жидкостях. Этим методом проводятся измерения значений указанных величин для разных масел (нефти), а также определяются температурные коэффициенты скорости звука и смолистость. Обговорюється лазерне генерування звукових хвиль у сильно поглинальних рідинах. Ми демонструємо експериментальну методу для одночасного визначення швидкості звуку та коефіцієнта поглинання світла у рідинах. Цією методою проводяться міряння значень зазначених величин для різних олив (нафти), а також визначаються температурні коефіцієнти швидкості звуку та смолистість.